Optimal feedback control of a twin rotor MIMO system. (2nd January 2017) - Choudhary, Santosh Kumar
Abstract : In this article, optimal feedback control of the twin rotor multiple input–multiple output (MIMO) system is investigated. The twin rotor MIMO system is a benchmark aero-dynamical laboratory model having strongly nonlinear characteristics and unstable coupling dynamics which make the control of such system for either posture stabilization or trajectory tracking a challenging task. This article first briefs the mathematical model of the twin rotor MIMO system and then illustrates the basic idea and technical formulation for controller design. The paper briefly explains the mixed sensitivity design method for feedback control of the twin rotor multiple input–multiple output system laboratory model. This approach has been considered in order to assure high control performance of the system. The simulation results show that the investigated controller has both static and dynamic performance, therefore the stability and the quick control effect can be obtained simultaneously for the twin rotor MIMO system.